PRINCIPLES AND MODEL OF ASSESSMENT IN THE EFL CLASSROOM - Tahrun Tahrun (ELTE Journal (English Languange Teaching and Education), 2014)
AbstractThis article presents the fundamental principles and model of assessment in the EFL classroom. A test as an assessment instrument on EFL classroom is designed to collect information of student learning progress. This instrument should meet the five principles: practicality, reliability, validity, authenticity, and washback. The process of assessment can   be implemented in three ways: teaching/learning-test, teaching/learning-test- teaching/learning-test, and paralyzed assessment with teaching/learning throughout the course.  Teachers often find difficulties to meet all of the principles in their teaching context. Consequently, they should be able to choose what principles they emphasize. Different choices can occur because they have different teaching context. It means that teaching context faced by the teachers will influence the options of principles to apply in assessment. Key Words: assessment, test, assessment principles, assessment model and EFL classroom